Associated Factors of Loneliness Among Adolescents in Indonesia during the Pandemic of Covid-19 - Panggaribuan, Santa Maria; Yemina, Loritta; Widiastuti, Sri Hunun; Purborini, Nurul; Casman , Casman (Universitas Muhammadiyah Surakarta, 2024)
Outbreak of Corona virus disease (Covid) in 2020 affected people’s life, particularly adolescents. Loneliness was one of the problems that adolescents faced during the outbreak of Covid-19. Loneliness could affect adolescents health, both mental and physical health. On the other hands, there were a lot of factors that related to loneliness among adolescents. Therefore, the purpose of this study was to explore the factors associated with loneliness in adolescents in Indonesia during the Covid-19 pandemic. Methodology this study was a cross-sectional study. The respondents in this study were 590 adolescents. This study was using some questionnaires that distributed online by social media. The questionnaire included the Connor Davidson Resilience Scale (CD-RISC)-25, the UCLA loneliness Scale version 3, and demographic characteristics. Hierarchical linear regression was performed to investigate the determinant factors of loneliness among adolescents. Results this current study found that age group of 16-19 YO (β = .117); female adolescents (β = .095); trust in one’s instincts, tolerance to negative affect, and strengthening effects of stress (β = .130); and spiritual influence (β = .094) were associated with increasing loneliness in adolescents. For the positive acceptance of change, and secure relationship (β = -.289); and control (β = -.273) were associated with lower likelihood of having loneliness. Conclusion this current study found that age group of 16-19 YO; female adolescents; trust in one’s instincts, tolerance to negative affect, and strengthening effects of stress; and spiritual influence were associated with increasing loneliness in adolescents. For the positive acceptance of change, and secure relationship; and control were associated with lower likelihood of having loneliness. The current results, particularly the identification of associated factors, should be useful for developing loneliness-prevention program.